IMPACT OF IMPLEMENTING PERFORMANCE-BASED INCENTIVE PROGRAMS ON IMPROVING HEALTHCARE QUALITY AND OUTCOMES - Sami Fahd M Al Motery, Naif Ghubyashan Alsuhaymi, Abdullah Mastour Almuhyamdi, Yasir Ali Alsuhaymi, Ibrahim Hamad Alrashidi, Esaam Mohammed Shaker, ,; Yousif Ayed Alharbi, Abdulrahman Saleh Aldaham, Maha Mesfer Alasmari, Hanadi Baker Albarnawi, ,; Abdullah Nasser Alrasheed, Bader Fahad Hajed Alharbi, Nasser Saeed Alqahtani, Waleed Moed Samar Almutairi, Mohammed Atiah Aldhafeeri, (Chelonian Research Foundation, 2022)
Many nations have implemented performance-based incentives to address increasing expenses and concerns over safety, quality, fairness, and affordability in healthcare. These incentives are designed to target both healthcare institutions and people. The impact of these initiatives has yielded inconclusive evidence. It is still uncertain how successful techniques, with different designs and levels of size compared to provider remuneration, are in motivating individual-level performance. This paper examines the existing data about the efficacy of individual-level performance-based incentives for healthcare in Organisation for Economic Co-operation and Development (OECD) countries. These countries are ideally positioned to establish, monitor, and evaluate programs that use performance-based incentives. We specify the circumstances in which penalties or incentives, in relation to the pursuit of gains, the avoidance of losses, and the heightened societal pressure to change behaviors, may be more successful. We have discovered that programs mostly use positive reinforcement mechanisms, with a somewhat higher number of bonus incentives compared to incentives based on payment per output or result attained. Upon comparing the results obtained from negative reinforcement techniques with positive reinforcement techniques, we have discovered a greater body of data supporting the effectiveness of positive reinforcement methods in enhancing the performance of healthcare workers. In general, slightly more than half of the studies indicated favorable effects, highlighting the need of careful consideration in the development and implementation of performance-based incentive programs. Keywords: Pay for performance, Performance-based rewards, Healthcare professionals, Organisation for Economic Co-operation and Development (OECD).